History of the Madrid nursing school «Salus Infirmorum» - María Teresa Miralles Sangro; E. Garre Murúa; Francisca Casas Martínez; Teresa Ruiz Ureña; Purificación González Villanueva (Universidad de Alicante, 1997)
The aim of the present study is first: to describe the origin of the Nursing School «Salus Infirmorum», opened in Madrid in 1943, with its specific characteristics. According to our personal opinion the School has been faithful to its origin. Second: to discover its evolution from the beginning up to the present time. We started by giving a retrospective view to the socio-sanitary care in the Madrid after-war, as well as to regarding the Institutions and Social Organizations in charge of the nursing education at that time. Sources used were: Bibliographical revisions. Rules, Legislations, Laws, periodical publications and original documents available in the «Salus Infirmorum» School, as well as personal interviews built up for the purpose and biographical interviews. The study shows the most significant stages and evolution of the Nursing School: The Institution Salus Infirmorum. The lady founder. The Opening of the School. Further Study Programme. Nursing-ATS School. Nursing School attached to University. The results show as the most significant facts: - The Nursing School of «Salus Infirmorum» appears to cover the education needs of a very special moment and far from extinguishing later on, the School adapts itself to the social reality of the present time. - From its foundation, the School of «Salus Infirmorum» has been faithful to the aims of its conception: To furnish the student with scientific, technical, human, ethic and Christian education and criteria.